Faktor-faktor Determinan Plasenta Akreta Di RSUD dr. Saiful Anwar Pemerintah Provinsi Jawa Timur - Endang Mudayati; Waifti Amalia; Jiarti Kusbandiyah (LPPM Widyagama Husada Malang, 2026)
Abstract Placenta accreta is a severe obstetric complication characterized by abnormal adherence of the placenta to the uterine wall, which may lead to massive hemorrhage and maternal death. The incidence of placenta accreta continues to rise in parallel with increasing rates of cesarean sections and other uterine surgical procedures. This study aimed to identify the determinant factors influencing the occurrence of placenta accreta. This research employed a retrospectiv analytic design with a cross-sectional approach. The sample consisted of 90 pregnant women selected through random sampling, based on medical records from 2022 to 2024. Data collection used an observation sheet based on the Placenta Accreta Index (PAI) and analysis was performed using the Chi-Square test. The results showed a significant association between placenta accreta and history of cesarean section (p = 0.004), maternal age >35 years (p = 0.024), and history of other uterine surgical procedures (p = 0.028). Meanwhil parity, placenta previa, and gestational hypertension were not significantly associated. It is concluded that maternal age, cesarean history, and previous uterine procedures are key determinants of placenta accreta. These findings are expected to contribute to risk screening and delivery planning for high-risk pregnant women.